Papillary renal cell carcinoma within a renal oncocytoma: case report of an incidental finding of a tumour within a tumour. Issue 4 (3rd April 2007) - Rowsell, Corwyn; Fleshner, Neil; Marrano, Paula; Squire, Jeremy; Evans, Andrew
Abstract : The most common renal tumours are clear cell, papillary, chromophobe and collecting duct renal cell carcinomas (RCCs), and benign oncocytomas and angiomyolipomas. Tumours with hybrid features between some of these entities have been recognised; in particular, tumours with features of both chromophobe RCC and oncocytoma. Case reports describing one distinct type of primary renal tumour actually within another are very rare. The incidental finding of a papillary RCC located in an oncocytoma in a nephrectomy specimen from a 75-year-old man is described. Morphological criteria for each tumour type were completely satisfied and fluorescence in situ hybridisation detected the expected number of copies of chromosome 7 in the cells of each tumour type. The cells in the papillary tumour contained three copies, whereas the oncocytoma cells contained only two per nucleus. To our knowledge, this is the first report of a papillary RCC being identified within an oncocytoma.